Innovations in Glaucoma Surgeries - Vanita Pathak Ray; Rahila Ramzan (Delhi Journal of Ophthalmology)
Several modalities may be used in the treatment of glaucoma - including medical, laser and surgical. Surgical treatment has so far been sub-conjunctival in nature and bleb-dependent, with inherent limitations despite being efficacious. This article focuses on the newer glaucoma procedures, viz-a-viz microinvasive glaucoma surgeries (MIGS) that have recently been deployed with favourable results. MIGS works via various mechanisms, by-passing trabecular meshwork by implanting a stent or excising the trabecular tissue, enhancing aqueous outflow through Schlemm’s canal or, shunting the aqueous to the suprachoroidal space. As such it has become mostly ab-interno which has enhanced its safety profile making it suitable for use in mild-to-moderate glaucomas i.e. much earlier on in the disease spectrum. The majority of the ab-interno procedures and devices require a mastery of intra-operative gonioscopy.